(untitled) (Research, Society and Development, 2022)
This study aimed to conduct a market research on Italian type salami, and evaluate sensory, physical and chemical characteristics of 4 brands sold in Dourados -MS. The market research was carried out using the form Google Form® form, sensory analysis (acceptance test and purchase intention), and physical and chemical (water activity (Aw), pH, color and shear strength). The survey reached 14 states of various age groups, with fixed incomes of four or more minimum wages, and only 8% of these had some restriction on the consumption of salami, 2% being vegetarian. The most consumed type of salami was the Italian type, and 64% of them could easily find it in the market. The most popular brands were Sadia, Seara and Perdigão. As for the attributes odor and color, the average varied from "I liked it moderately" to "I liked it a lot", for flavor, from "I liked it a little to I liked it a lot" and texture, all of them obtained average ratings of "I liked it moderately". The intention to certainly buy ranged from 26% (sample 3) to 60% (sample 1). The Aw values met the legislation. The values of the L* parameter varied from 48.26 to 55.17, a* from 12.23 to 15.07, b* from 7.02 to 9.00, hue from 24.98 to 33.05° and Chroma from 14.18 to 16.63. Sample 1 obtained the highest value of shear force, differing from the others. It can be concluded that commercial Italian type salamis have differences that can be decisive in the consumer’s choice. These differences are due to the variations in the preparation method adopted by the brands in their productions.